English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

The equations are

(3√5 – 7) (√5+2)

and

15√72 - 4√98

2007-04-25 09:12:49 · 12 answers · asked by jane d 1 in Science & Mathematics Mathematics

12 answers

1.)1-√5 ....answer

(3√5 – 7) (√5+2)
(3*5+6√5-7√5-14)
(15+(6-7)√5-14)
(1-√5)

2.) 62* √2....answer

15√72 - 4√98
(15√(3^2 *2^2 *2) ) -(4√(7^2 *2))
15*3*2*√2 - 7*4*√2
90√2 -28√2
√2( 90-28)
62√2

2007-04-25 09:31:09 · answer #1 · answered by priya 2 · 0 0

First of all, these aren't equations. They're just expressions. So there's nothing to "solve". But you can SIMPLIFY them.

For the first one, just use the "FOIL" technique or the distributive rule twice:
(3√5 - 7) (√5+2) =
3√5√5 - 7√5 + 6√5 - 14 =
3*5 - 7√5 + 6√5 - 14 =
15 - √5 - 14 =
1 - √5

For the second one, try to factor out numbers that are perfect squares:
15√72 - 4√98 =
15√(9*8) - 4√(49*2) =
15*3√8 - 4*7√2 =
45√8 - 28√2 =
45√(4*2) - 28√2 =
45*2√(2) - 28√2 =
90√2 - 28√2 =
62√2

2007-04-25 09:29:52 · answer #2 · answered by Anonymous · 0 0

These are not equations but are expressions. You can tell because there is no = sign anywhere. We can simplify these expressions as follows:
(3√5 – 7) (√5+2)
= (3√5(√5) +6(√5) – 7√5-14
3*5-√5 - 14 = 1 - √5

15√72 - 4√98
15√(36*2) - 4√(49*2)
= 15*6√2 - 4*7√2
=90√2 - 28√2 = 62√2

2007-04-25 09:27:41 · answer #3 · answered by ironduke8159 7 · 0 0

(3√5 – 7) (√5+2) =
3√5(√5+2) - 7(√5+2) =
3(√5)² + 6√5 - 7√5 - 14 =
3*5 - √5 - 14 =
15 - 14 - √5 = 1 - √5
Resposta: 1 -√5
><
15√72 - 4√98
72|2
36|2
18|2
09|3
03|3
01
√72 = 2³ * 3²
98|2
49|7
07|7
01
√98 = 2 * 7²
So,
15√72 - 4√98 =
15 * √(2³*3²) - 4√(2 * 7²) =
(15*3*2√2) - (4*7* √2) =
90√2 - 28√2 = 62√2
Respsota: 62 times√2
:=:=:=:

2007-04-25 09:19:44 · answer #4 · answered by aeiou 7 · 0 0

Hello

(3√5 – 7) (√5+2) -- First step is to muliply.

Thus we get (3*5) + 6√5 - 7√5 - 14
Simplified this is 15 - √5 -14 ===== 1-√5

Next, 15√72 - 4√98
First step is to simplify to get 15(√36)(√2) - 4(√49)(√2)

This equals 15(6)(√2) - 4(7)(√2) == 90√2 - 28√2 = 62√2.

Hope this helps

2007-04-25 09:24:44 · answer #5 · answered by Jeff U 4 · 0 0

1)
(3√5 – 7) (√5+2)
=3√5*√5+3√5*2-7*√5-7*2
=15+6√5-7√5-14
=1-√5

2)
15√72 - 4√98
=(15√3*3*2*2*2)-4√7*7*2
=15*3*2√2-4*7√2
=90√2-28√2
=62√2

2007-04-25 09:20:38 · answer #6 · answered by Anonymous · 0 0

1- √5 and

90√2 - 14√2 = 62√2

2007-04-25 09:33:31 · answer #7 · answered by jonesdollesin 1 · 0 0

a million.Ember Grace or Arielle June 2. Willow Jane or Madelyn Quinn 3. Kiera Giselle 4. Emmy Katherine 5. Heather June or Bethany exhilaration 6. not good options yet Gorgia Kaia 7. Gemma Paige

2016-10-30 06:55:51 · answer #8 · answered by Anonymous · 0 0

3*5 -14 +6√5 - 7√5

15 -14 -√5 = 1-√5

2007-04-25 09:20:03 · answer #9 · answered by Anonymous · 0 0

i think the top one is 3 times the square root of 5-7 times the square root of 5+2 right? then its 1.3475237

the bottom should be 9.8994949

2007-04-25 09:19:39 · answer #10 · answered by jamz 5 · 0 1

fedest.com, questions and answers